2022
DOI: 10.3390/su14159105
|View full text |Cite
|
Sign up to set email alerts
|

Building Students’ Entrepreneurial Competencies in Chinese Universities: Diverse Learning Environment, Knowledge Transfer, and Entrepreneurship Education

Abstract: Entrepreneurship education is a critical issue for higher education (HE) students, and thus has been on the agenda of national sustainable development in China. However, few studies have approached the enhancement of HE students’ entrepreneurial competencies in relation to the perspective of their learning environment. This study developed and employed the Theoretical Model of Entrepreneurial Competencies to examine the path of improving HE students’ entrepreneurial competencies. The results reveal that a dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 62 publications
0
5
0
1
Order By: Relevance
“…Costin, O'Brien & Hynes (2022) analysed the effects of entrepreneurship education on aptitude, entrepreneurial confidence, self-efficacy, students' belief in their motivation and ability to start an entrepreneurial venture. In the study by Chen, Tang & Han (2022) it was confirmed the entrepreneurship education significantly moderated the effects of self-efficacy on higher education students' entrepreneurial competencies. Cognitive flexibility, self-efficacy, and knowledge transfer mediate this relationship.…”
Section: Students' Entrepreneurial Competenciesmentioning
confidence: 83%
“…Costin, O'Brien & Hynes (2022) analysed the effects of entrepreneurship education on aptitude, entrepreneurial confidence, self-efficacy, students' belief in their motivation and ability to start an entrepreneurial venture. In the study by Chen, Tang & Han (2022) it was confirmed the entrepreneurship education significantly moderated the effects of self-efficacy on higher education students' entrepreneurial competencies. Cognitive flexibility, self-efficacy, and knowledge transfer mediate this relationship.…”
Section: Students' Entrepreneurial Competenciesmentioning
confidence: 83%
“…Differences in the physical learning environment, technology and infrastructure, social interaction in diverse learning environments can spur students' cognitive growth and strengthen their intellectual performance while developing critical thinking that contributes to the successful transfer of knowledge (Chen et al, 2022). The development of instrumental skills leads to an increase in competence arising from one's abilities (Mets et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Flexibility and adaptation, which are inherent in business bricolage, are critical in learning and knowledge acquisition. Bricolage entrepreneurs must be open to new ideas, willing to learn from mistakes and fast to modify their methods (Chen, Tang, & Han, 2022). This adaptability encourages an attitude of constant learning, allowing entrepreneurs to gain knowledge from a variety of sources.…”
Section: Bricolage and Entrepreneurial Knowledgementioning
confidence: 99%